2020
DOI: 10.1039/c9ra10200k
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a forming process on the properties and structure of RANEY®-Ni catalysts for the hydrogenation of 1,4-butenediol

Abstract: Xianlong Gao's paper focuses on the effects of a forming process on the catalytic hydrogenation of 1,4-butenediol (BED) to produce 1,4-butanediol (BDO). The evaluation results showed that the RNAA catalyst showed excellent hydrogenation performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…e catalyst employed in the study is a granular sponge nickel type. Previous studies on the hydrogenation mechanism on Raney Ni found that catalyst activity is proportional to active Ni sites (Mikkola et al, 2000;Gao et al, 2020). Hence, in this study, hydrogenation presumably happens on the catalyst surface, speci cally on active nickel sites.…”
Section: E Ect Of Ni Catalyst and Feed Concentrationmentioning
confidence: 55%
“…e catalyst employed in the study is a granular sponge nickel type. Previous studies on the hydrogenation mechanism on Raney Ni found that catalyst activity is proportional to active Ni sites (Mikkola et al, 2000;Gao et al, 2020). Hence, in this study, hydrogenation presumably happens on the catalyst surface, speci cally on active nickel sites.…”
Section: E Ect Of Ni Catalyst and Feed Concentrationmentioning
confidence: 55%
“…However, here the hydrogenation was performed at 70 °C. Nonetheless, a small amount of aluminum ( � 10 wt%) present in the catalyst may have acidic nature, [50] and thus it could catalyze the double bond activation while Ni could promote CÀ C hydrogenolysis. Interestingly, CÀ C hydrogenolysis was observed only for eugenol and could be thus linked to the presence of the double bond because hydrogenolysis was not detected in case of 4propylphenol hydrogenation.…”
Section: Effect Of the Methoxy Groupmentioning
confidence: 99%
“…7 To overcome the above obstacle, it is necessary to develop efficient catalysts, particularly economical catalysts such as Ni, which can ensure the fast and directional conversion of the BED intermediate to BDO. 6,8 Although the intrinsic hydrogenation activity of Ni is always inferior to that of precious metals (Pd, Pt, Ru, etc. ), it is believed that nano-Ni-catalysts can also exhibit a benign hydrogenation property via the modification of metal synergy, support features, or acidity and the metal−support interaction.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome the above obstacle, it is necessary to develop efficient catalysts, particularly economical catalysts such as Ni, which can ensure the fast and directional conversion of the BED intermediate to BDO. , Although the intrinsic hydrogenation activity of Ni is always inferior to that of precious metals (Pd, Pt, Ru, etc. ), it is believed that nano-Ni-catalysts can also exhibit a benign hydrogenation property via the modification of metal synergy, support features, or acidity and the metal–support interaction. , Concerning the support effects on BYD hydrogenation, Rode et al investigated the effects of different supports including C, Al 2 O 3 , SiO 2 , and CaCO 3 on the enhancement in activity and selectivity of BYD hydrogenation, and they pointed out that different metal–support interactions significantly affected H 2 adsorption, leading to various hydrogenation performances and product distributions .…”
Section: Introductionmentioning
confidence: 99%